WASPAS Implementation on Digital Talent Scholarship Selection - Muhammad Dahria; Saiful Nur Arif; Badrul Anwar (The IJICS (International Journal of Informatics and Computer Science), 2022)
Digital transformation also greatly influences the direction of economic development in Indonesia. This has an impact on the increasing need for IT experts, especially in the programming field. However, the number of skilled and reliable human resource programmers in Indonesia is still very small and has not been able to meet the demands of the digital industry. Therefore, information technology and decision support systems are needed as a tool to determine the selection of qualified junior mobile programming talent. As in previous research, a decision support system is a system specifically designed for the decision-making process on semi-structured and unstructured problems. In order for the purpose of the decision support system to be realized properly, it is assisted by using one of the methods in the decision support system, namely the WASPAS method which is a combination of the WSM and WPM methods. This method can be used to solve MCDM (Multi Criteria Decision Making) problems